Analysis of post-crisis accounting profession readiness - Nurhasanah, Nunung; Astuti, Ernasari Widy; Rokhman, Fathur; Prawira, Andi Raditya (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The post-crisis pandemic outbreak has changed the order of life. In this new post-crisis era, various challenges arise, including in the accounting profession. This research aims to determine the skill standards needed to carry out the accounting profession in the new normal conditions. This standard is in line with data on job market demand for beginners in the accounting profession disclosed on the job vacancy site Jobstreet. The population and sample for this study were 151 job vacancies, including the categories